Corporate entrepreneurship and innovation performance: The mediating effect of employee engagement through leader's supervision - Fatma Makhlouf Cherif (Economies, 2022)
The purpose of this paper was to investigate the mediated moderating effect of employee engagement (EE) by leader's supervision in the effects of corporate entrepreneurship (CE) on innovation performance (IP). The study applied the cross-sectional analysis with our own survey that provided the data for this design. A total of 248 participants (12 managers, and 236 employees) were recruited for this study. The relationship of CE and IP was mediated by EE. Additionally, leader's supervision moderated the relationship between CE and IP. Furthermore, leader's supervision had a mediated moderation effect from CE to the IP, through the EE. The significance of this study lies in its contribution to CE, IP, EE and leader's supervision literatures. It was revealed that CE behavior was found in the organizational learning processes that strengthen employees' ability to analyze markets and formulate new products.
Keywords: 330; corporate entrepreneurship; employee engagement; innovation performance; leader's supervision; mediating effect